Optimization of ultrasound-assisted enzymatic extraction and in vitro antioxidant activities of polysaccharides extracted from the leaves of Perilla frutescens - LI,Huizhen (2020)
Abstract A Box-Behnken design was employed to optimize ultrasound-assisted enzymatic extraction of polysaccharides from perilla leaves. Four independent variables, namely, liquid-to-solid ratio, enzymatic time, enzymatic temperature, and ultrasonic power were investigated. Under the optimal liquid-to-solid ratio of 41:1, enzymatic time of 40 min, enzymatic temperature of 49 °C, and ultrasonic power of 204 W, the experimental polysaccharide yield was 3.84% (n = 3), which was close to the value predicted by response surface methodology (3.9%). Four polysaccharides (PLP1, PLP2, PLP3, and PLP4) were obtained with DEAE-cellulose-52 and Sephadex G-100 chromatography, and their antioxidant activities were investigated with various antioxidant assays in vitro. All the four polysaccharides possessed good antioxidant properties in a concentration-dependent manner, and PLP3 presented the highest antioxidant activity. Thus, the novel polysaccharides extracted from perilla leaves could be promising bioactive macromolecules that can be applied as potential antioxidants in medical and food industries.